From ideas of power to the powering of ideas in organizations: Reflections from Follett and Foucault. Issue 6 (December 2020) - Carlsen, Arne; Clegg, Stewart R.; Pitsis, Tyrone S.; Mortensen, Tord F.
Abstract: Research on organizational creativity tends to emphasize fairly static notions of coercive power as positional authority and control over scarce resources. The field remains largely silent about power as a positive and generative phenomenon that can produce creativity . We seek to break that silence by amplifying and integrating the work of Mary Parker Follett and Michel Foucault in concert with recent practice-based approaches to creativity. Power in organizational creativity, we suggest, should first of all be explored as processes of connection, abundance and collective agency. We show that whereas established ideas of positional power over is related to assumptions of linearity and singularity of creativity, ideas of power with and power to are associated with a more dynamic, relational and process-based perspective. The latter set of views implies more attention be paid to processes of interactional framing through which people jointly attend to situations, reach new integrations and produce new social realities.